Effects of interval training on quality of life and cardiometabolic risk markers in older adults: a randomized controlled trial - Ballin M (Dove Medical Press, 2019)
Marcel Ballin1,2, Emmy Lundberg1,2, Niklas Sörlén1,2, Peter Nordström1, Andreas Hult2, Anna Nordström2,3 1Department of Community Medicine and Rehabilitation, Unit of Geriatric Medicine, Umeå University, Umeå, Sweden; 2Department of Public Health and Clinical Medicine, Section of Sustainable Health, Umeå University, Umeå, Sweden; 3Department of Sport Science, School of Sport Sciences, The Arctic University of Norway, Tromsø, NorwayCorrespondence: Anna NordströmDepartment of Public Health and Clinical Medicine, Section of Sustainable Health, Umeå University, Umeå 901 85, SwedenTel +46 70 606 4249Email anna.h.nordstrom@umu.sePurpose: To explore the effects of 10 weeks of progressive vigorous interval training as a single intervention on health-related quality of life (HRQoL) and cardiometabolic risk markers in centrally obese 70-year-old individuals.Participants and methods: A randomized controlled trial (ClinicalTrials.gov registration no. NCT03450655) including seventy-seven community-dwelling 70-year-old men and women with central obesity defined as > 1 kg visceral adipose tissue for women and > 2 kg for men. Participants randomized to the intervention group were offered a 10-week progressive vigorous interval training program performed three times per week. Control subjects were asked to maintain their daily living and routines throughout the trial. All participants in both groups had received tailored lifestyle recommendations focused on diet and physical activity at one occasion within 12 months prior to trial initiation. Prespecified outcome measures included: changes in HRQoL using the Short Form Health Survey Questionnaire (SF-36), blood pressure; resting heart rate (HR) and blood lipids. All analyses were conducted on an intention-to-treat basis.Results: The intervention resulted in significant effects on the SF-36 mental component summary (MCS) score and the mental health (MH) subscale (P< 0.05 for both), when compared to the control group. Specifically, the intervention group increased their MCS score by 6.3 points (95% confidence interval [CI] = 0.3–12.3) and their MH score by 6.0 points (95% CI = 1.7–10.4) compared to the control group. Moreover, significant effects were seen on resting HR, total cholesterol and LDL-cholesterol (P<0.05 for all).Conclusion: It was shown that 10 weeks of vigorous interval training as a single intervention was sufficient to improve mental aspects of HRQoL in older individuals with central obesity, which is a critical aspect of healthy ageing. Positive effects were seen also on cardiometabolic risk markers.Keywords: exercise, ageing, perceived health, blood lipids